2005
DOI: 10.1002/jnr.20514
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteic acid induces intraneuronal accumulation of neurotoxic Aβ42: Implications for the pathogenesis of Alzheimer's disease

Abstract: The causes of neuronal dysfunction and degeneration in Alzheimer's disease (AD) are not fully understood, but increased production of neurotoxic forms of amyloid beta-peptide-42 (Abeta42) seems of major importance. Large extracellular deposits of aggregated Abeta42 (plaques) is a diagnostic feature of AD, but Abeta42 may be particularly cytotoxic when it accumulates inside neurons. The factors that may promote the intracellular accumulation of Abeta42 in AD are unknown, but recent findings suggest that individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 46 publications
2
63
0
Order By: Relevance
“…The association of homocysteine with disease states in which oxidative stress is a key component of the pathology is undisputed [22,23,[28][29][30]. Further there have been considerable studies in which homocysteine has been suggested to directly contribute to the oxidative stress [25,28,29,[34][35][36][37][38]. The suggestion that homocysteine can itself generate H 2 O 2 , with the assistance of Copper, has provided a proposed mechanism for this contribution [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of homocysteine with disease states in which oxidative stress is a key component of the pathology is undisputed [22,23,[28][29][30]. Further there have been considerable studies in which homocysteine has been suggested to directly contribute to the oxidative stress [25,28,29,[34][35][36][37][38]. The suggestion that homocysteine can itself generate H 2 O 2 , with the assistance of Copper, has provided a proposed mechanism for this contribution [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In models of Alzheimer's disease homocysteine enhances the toxicity of the amyloid-ß peptide [34][35][36][37]. The strong links between homocysteine [38] and neurodegenerative disease suggests that these models would be useful to study if homocysteine has any action on catalase.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that homocysteic acid (HA) is the probable pathogen of AD in blood [14][15][16][17], and it increases BBB permeability by NMDA receptor activation [18]. Especially it is interesting that HA can induce the amyloid β-42 which accumulated into neuronal cell [17].…”
Section: Citationmentioning
confidence: 99%
“…Especially it is interesting that HA can induce the amyloid β-42 which accumulated into neuronal cell [17]. HA is known as a glutamate receptor agonist [19].…”
Section: Citationmentioning
confidence: 99%
“…Elevated homocysteine levels in the blood or CSF of human subjects has been linked to an increased risk for AD (reviewed in : Zhuo et al, 2011(Zhuo et al, 2011, and this link between elevated levels of homocysteine and AD-like pathology or cognitive impairment has been reproduced in cell and animal models (Bernardo et al, 2007;Fuso et al, 2012b;Hasegawa et al, 2005;Kruman et al, 2002;Pacheco-Quinto et al, 2006;Rhodehouse et al, 2013;Sontag et al, 2007;Wei et al, 2011;Zhang et al, 2009;Zhuo et al, 2010;Zhuo and Pratico, 2010a, b). Several potential mechanisms have been proposed to explain the link between hyperhomocysteinemia and AD including oxidative stress, cerebrovascular damage, altered DNA methylation, Aβ elevation and tau protein phosphorylation (Fleming et al, 2012;Fuso et al, 2012a;Marlatt et al, 2008;Sontag et al, 2007;Sontag et al, 2008;Troen et al, 2008;Wei et al, 2011;Zhang et al, 2009;Zhuo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%